Blood Pressure Profile in School Children (6–16 Years) of Southern India: A Prospective Observational Study - Sayeemuddin, Mohammad; Sharma, Deepak; Pandita, Aakash; Sultana, Tabassum; Shastri, Sweta (Frontiers in Pediatrics, 2015)
Aims and objective: To determine normal blood pressure (BP) in apparently healthy, asymptomatic school children in the age group of 6–16 years and to determine the correlation of BP values with different sex, weight, height, and body mass index (BMI) and also to find out prevalence of hypertension in school going population. Materials and methods: This prospective, observational study enrolled 3,302 urban children (1,658 boys and 1,644 girls) in the age group of 6–16 years. These were analyzed to study the distribution pattern of systolic blood pressure (SBP) and diastolic blood pressure (DBP) at different ages, sex, weight, height, and BMI. The SBP and DBP were noted as per age and sex. The association was seen between mean SBP and mean DBP with weight, height, and BMI. Information was collected about the family history of hypertension and was correlated with the obtained SBP and DBP readings. Results: The mean SBP in males at 6 years was 99.69 ± 3.62 mm of Hg, at 10 years was 102.20 ± 2.16 mm of Hg, and at 16 years was 115.33 ± 1.26 mm of Hg. The mean SBP in females at 6 years was 96.55 ± 2.86 mm of Hg, at 10 years was 101.16 ± 2.12 mm of Hg, and at 16 years was 112.41 ± 1.06 mm of Hg. The correlation coefficient for relationship between age and SBP in males and females was 0.89 and 0.91, respectively, and for DBP was 0.92 and 0.90, respectively. The correlation coefficient for relationship between height and SBP in males and females was 0.91 and 0.93, respectively, and for DBP was 0.92 and 0.88, respectively. The correlation coefficient for relationship between weight and SBP in males and females was 0.92 and 0.92, respectively, and for DBP was 0.94 and 0.91, respectively. In the nomogram obtained in the study, 95% of study population fall between mean +2SD and −2SD. Conclusion: The blood pressure (BP) (SBP and DBP) tends to increase with age, weight, height, and BMI. The BP values (SBP and DBP) increases grossly after 11 years of age. The students with positive family history of hypertension had higher valve when compared to other student. The BP of children and adolescents can be evaluated using the reference table according to age. The table provided helps to classify as “normal” or “hypertension” (>+2SD).